Is diminished ovarian reserve a risk factor for miscarriage? Results of a systematic review and meta-analysis. (13th July 2021) - Busnelli, Andrea; Somigliana, Edgardo; Cirillo, Federico; Levi-Setti, Paolo Emanuele
Abstract: BACKGROUND: Anti-Müllerian hormone (AMH) serum concentration and antral follicle count (AFC), as measured by transvaginal ultrasonography, accurately reflect the antral follicle pool. However, AMH and AFC association with fertility surrogates (i.e. age at menopause, probability of conceiving naturally and ART success rate) is questioned. Miscarriage is often considered an alternative measure of reproductive capacity. Nonetheless, the impact of diminished ovarian reserve (DOR) on miscarriage incidence remains an understudied and unresolved issue. OBJECTIVE AND RATIONALE: The aim of this systematic review and meta-analysis was to elucidate associations between DOR and miscarriage risk, both in women who conceived naturally and in those who achieved pregnancy through ART. SEARCH METHODS: Relevant studies were identified by a systematic search in PubMed, MEDLINE, Embase and Scopus, from database inception to 1 March 2021. Studies were included only if all the following conditions were met: DOR was defined using serum AMH concentration or AFC; miscarriage rate was reported separately for different groups of women categorized according to the AMH and/or AFC level; authors reported either the rate of intrauterine pregnancy loss before 22 weeks of gestation or enough data were available to calculate it. OUTCOMES: From a total of 347 publications initially identified, 16 studies were included. Pooled results from 13 retrospective studies focusing on ART pregnancies showed a significantly higher rate of miscarriage in women with a low AMH, as compared to women with a medium or high serum AMH concentration (12 042 women, random effects model, odds ratio (OR) 1.35; 95% CI, 1.10–1.66; P = 0.004; I 2 =50%). The only prospective study on ART pregnancies failed to show any association (61 women, risk ratio (RR) 2.95; 95% CI, 0.66–3.18; P = 0.16). Data from two prospective studies, which included naturally conceived pregnancies, showed a significantly increased miscarriage risk for women with low serum AMH. However, these data could not undergo meta-analysis owing to differing study designs. Using three retrospective studies, we observed an association between low AFC and miscarriage incidence (three retrospective studies on ART pregnancies, random effects model, OR 1.81; 95% CI, 1.02–3.21; P = 0.04; I 2 =64%). WIDER IMPLICATIONS: Our meta-analysis findings suggest that within the DOR patient subgroup, serum AMH and AFC biomarker levels may correlate with both the quantitative and qualitative aspects of ovarian reserve. However, owing to study limitations, the aetiology of this effect remains unclear and we are unable to define a causal relationship between DOR and increased miscarriage or to provide clinical recommendations based on this information. However, if confirmed by future well-designed studies, these findings would be profoundly informative for guiding women in family planning decisions.